Path-independent digital image correlation with high accuracy, speed and robustness - Jiang, Zhenyu; Kemao, Qian; Miao, Hong; Yang, Jinglei; Tang, Liqun (Optics and lasers in engineering, 2015)
The initial guess transferring mechanism is widely used in iterative DIC algorithms and leads to path-dependence. Using the known deformation at a processed point to estimate the initial guess at its neighboring points could save considerable computation time, and a cogitatively-selected processing path contributes to the improved robustness. In this work, our experimental study demonstrates that a path-independent DIC method is capable to achieve high accuracy, efficiency and robustness in full-field measurement of deformation, by combining an inverse compositional Gauss–Newton (IC-GN) algorithm for sub-pixel registration with a fast Fourier transform-based cross correlation (FFT-CC) algorithm to estimate the initial guess. In the proposed DIC method, the determination of initial guess accelerated by well developed software library can be a negligible burden of computation. The path-independence also endows the DIC method with the ability to handle the images containing large discontinuity of deformation without manual intervention. Furthermore, the possible performance of the proposed path-independent DIC method on parallel computing device is estimated, which shows the feasibility of the development of real-time DIC with high-accuracy. •This paper proposes a path-independent DIC method.•The proposed DIC method reaches high measurement accuracy at sub-pixel level.•The proposed DIC method shows excellent robustness for deformation discontinuity.•This work demonstrates the feasibility of real-time DIC with high accuracy.